Ma'had Al-Mubarak Al-Islami Tahtul Yaman Jambi and Malaysian Santri in the Malay Kinship System - Supian; K.A. Rahman (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2020)
This research reveals Malay cultural kinship in the ASEAN region, especially in Indonesia, Malaysia, Brunei Darussalam which can be seen in the exchange of students or santri from several allied countries who study or study in neighboring countries, such as Malaysian and Bruneian students. Darusalam who studied and memorized the Koran at Ma'had Al-Mubarak Al-Islami Litahfizhil Quran Al-Karim Tahtul Yaman Jambi. The large number of students from the neighboring country in Jambi is not only an element of kinship and cultural closeness among allied nations but also have their own motivation because of the kinship. This research will look at how the condition of Ma'had Al-Mubarak Al-Islami Litahfizhil Quran Al-Karim Tahtul Yaman Jambi and the motivation of these students so they choose and feel at home studying in Jambi. This motivation consists of a number of affinities such as language, religious schools or sects as well as customs and culture, so that they feel comfortable and feel at home studying in Jambi. Ma'had Al-Mubarak Al-Islami is interesting because it is the destination for students from Malaysia and Brunei Darussalam to study in Jambi. Keywords: Kinship, Culture, Motivation, Students, Santri